Transportation project management - Tieman, Rob (John Wiley & Sons, Inc., 2023)
Approachable guide combining project management principles and proven best practices applied to transportation projects Transportation Project Management is a comprehensive and approachable work providing practical guidance on all aspects of managing transportation projects. It covers project management principles, practical applications, and proven best practices, all tailored specifically to the unique workflows of developing and designing transportation projects, from inception through to advertisement for construction. Detailed themes include technical competencies, industry constraints, organizational opportunities, and the range of soft skills necessary to be an effective leader in this role. This timely publication responds to recent trends in the industry, as transportation organizations become more project-centric in their strategic approach, to enable more efficient project and program delivery amidst increased spending on infrastructure. Some topics covered in Transportation Project Management include: The "Triple Constraint" of budget, scope, and schedule, and meaningful change management The transportation Project Development Process and its unique interdependencies, opportunities, and constraints Creating your project management plan, a living document providing guidance and clarification on how the project will be managed during development Organizational structures, establishing and understanding how your organization operates, including who makes what decisions Understanding the fundamental differences between projects, programs, and portfolios, enabling successful project management within any organizational structure Critical Project Management soft skills, including communication, time management, leading meetings, stakeholder engagement, influence management, and managing expectations Developing and leading focused, efficient, and effective project teams Partnering with consultants to manage risks, drive development, and increase quality Aimed at professional transportation project managers in both the public and private sectors, along with engineering undergraduate and graduate students in related programs of study, Transportation Project Management provides the foundations for practitioners to become great transportation project managers.